Role of Teaching Assistants in Upgrading Learning Quality in SMPN 20 Kendari - Yuliana Sain; Windari Yusriani; Muhamad Badrun; Yuliani Yuliani; Nur Haizan; Al Fatah Razak (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This service is motivated by the Education Assistance Activities Batch 3, as a form of implementation of the Learning Merdeka Campus Merdeka (MBKM) in the form of educational assistance that allows students to support their learning process in high school. The program is based on six months of face-to-face classes. This program will be carried out to determine whether there is an increase in learning outcomes after the educational assistance program is implemented at SMPN 20 Kendari. The methods used are classroom observation, teacher-student collaboration, and direct instruction, learning design, and learning assessment. As a result of these activities, the learning outcomes produced by students during the learning process increased significantly.